Systemic infections with Candida sp. and Aspergillus sp. in immunocompromised patients with hematological malignancies: current serological and molecular diagnostic methods - Buchheidt, Dieter; Skladny, Heyko; Baust, Corinna; Hehlmann, Rüdiger (Chemotherapy, 2000)
Within recent years, novel serological and molecular methods have been developed to improve the early diagnosis of invasive fungal infections especially in patients with malignant hematological diseases being at highest risk of developing these life-threatening infections. Early diagnosis is essential for adequate therapeutic management, which, however, often remains difficult since the diagnostic tools clinically used either lack specificity or sensitivity, or both at worst. The clinical value, the advantages and remaining problems of recently developed, more sensitive and specific serological assays and molecular methods are reviewed.
Gesehen am 19.05.2022